2018
DOI: 10.4103/jcis.jcis_59_18
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde Pyelogram during intended Cystogram: A Rare complication of a common procedure

Abstract: Inadvertent placement of the urinary catheter into the ureter can cause several complications. We describe a rare complication during cystogram due to unrecognized inadvertently placed urinary catheter in ureter, resulting in a life-threatening situation. A 47-year-old multiparous female underwent total laparoscopic hysterectomy for adenomyosis. During early postoperative period, she developed vesicovaginal fistula and transvaginal repair of fistula was done. During filling cystography done at 2 weeks, she dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…As most of the surgeons prefer catheter removal after confirming absence of leak on filling cystograms, we suggest cystogram should be performed under dynamic fluoroscopy to avoid inadvertent complications. [79] Salient features of management and newer trends have been highlighted in Table 3.…”
Section: The Principles Of Vesicovaginal Fistula Repairmentioning
confidence: 99%
“…As most of the surgeons prefer catheter removal after confirming absence of leak on filling cystograms, we suggest cystogram should be performed under dynamic fluoroscopy to avoid inadvertent complications. [79] Salient features of management and newer trends have been highlighted in Table 3.…”
Section: The Principles Of Vesicovaginal Fistula Repairmentioning
confidence: 99%
“…A recent literature review and case series by Luo et al 1 identified 23 cases of ureteric misplacement of catheters and our own review notes eight further cases since. 28 These can present as catheter-related problems such as pain, blockage or bypassing but also with systemic upset including sepsis and acute renal failure. Iatrogenic injuries of the ureter have been reported requiring stenting or surgical repair.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Ureteric catheterisation has also been noted to occur in suprapubic catheters and as result of diagnostic imaging. 7,10…”
Section: Introductionmentioning
confidence: 99%